2003
DOI: 10.1046/j.0931-2668.2003.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide linkage and QTL mapping in porcine F2 families generated from Pietrain, Meishan and Wild Boar crosses

Abstract: Summary Three informative pig F2 families based on European Wild Boar (W), Meishan (M) and Pietrain (P) crosses have been used for genome‐wide linkage and quantitative trait loci (QTL) analysis. Altogether 129 microsatellites, 56 type I loci and 46 trait definitions (specific to growth, fattening, fat deposition, muscling, meat quality, stress resistance and body conformation) were included in the study. In the linkage maps of M × P, W × P and W × M families, average spacing of markers were 18.4, 19.7 and 18.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 74 publications
7
92
0
1
Order By: Relevance
“…Alleles inherited from the naturalized Brazilian Piau breed were responsible for the decreased muscling traits. Geldermann et al (2003) observed the presence of QTL for HW and BSW at position 115 cM on SSC4 in a cross between wild boar and Pietrain pigs; the QTL for HW and BSW were responsible for 5.2% and 8.3% of the phenotypic variation, respectively. Possibly, these QTL are the same.…”
Section: Discussionmentioning
confidence: 99%
“…Alleles inherited from the naturalized Brazilian Piau breed were responsible for the decreased muscling traits. Geldermann et al (2003) observed the presence of QTL for HW and BSW at position 115 cM on SSC4 in a cross between wild boar and Pietrain pigs; the QTL for HW and BSW were responsible for 5.2% and 8.3% of the phenotypic variation, respectively. Possibly, these QTL are the same.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, in this study the three connected F 2 -designs of Geldermann et al (2003) were analysed jointly for muscling and growth traits using a multi-allele multi-QTL model. A large number of QTL was found compared to the separate analysis of crosses (see Geldermann et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…the same W boar was used to generate the W × P and the W × M cross. A detailed description of the design can be found in Geldermann et al (2003). The F 2 -individuals were phenotyped for numerous traits.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations